Principal’s Leadership in Building Students’ Character at SMA Negeri 3 Kayuagung - Saputra, Firman; Ahmad, Syarwani; Kesumawati, Nila (Yayasan Sembilan Pemuda Indonesia, 2023)
The purpose of this study is to analyze and describe the principal's leadership in building the character of students at SMA Negeri 3 Kayuagung, the constraints of the principal's leadership in building the character of students at SMA Negeri 3 Kayuagung and efforts to overcome obstacles to the leadership of the principal in building character students at SMA Negeri 3 Kayuagung. The research methodology used the descriptive qualitative method by using triangulation with data taken from observation, interviews, and documentation. The results showed that the principal's leadership in building the character of students at SMA Negeri 3 Kayuagung was carried out in 3 stages including planning to strengthen the character of the students at SMA Negeri 3 Kayuagung, implementing strengthening the character of students at SMA Negeri 3 Kayuagung and evaluating the implementation of a character-based curriculum for SMA Negeri 3 Kayuagung. This study found that the obstacles faced were from internal and external factors, namely the lack of awareness of students, teacher, and parent factors, and solutions that were not optimal in building the character of students.